Cutaneous Small/Medium CD4+ Pleomorphic T-Cell Lymphoma–Like Nodule in a Patient With Erythema Chronicum Migrans. (June 2016) - Celebi Cherukuri, Nil; Roth, Christine G.; Aggarwal, Nidhi; Ho, Jonhan; Gehris, Robin; Akilov, Oleg E.
Abstract : Abstract: CD4+ small/medium pleomorphic T-cell lymphoma is a relatively rare subtype of cutaneous lymphoproliferative disorder with an indolent clinical behavior. The place of this condition among lymphomas is debatable. The authors describe a rare case of the direct association of CD4 small/medium pleomorphic T-cell lymphoma–like solitary nodule with Borrelia burgdorferi infection in a 5-year-old boy, discuss the reactive nature of this condition, and emphasize the importance of clinicopathological correlation.